The effect of landscape authenticity, nature-based experiences, tourist participation in the preservation of tourist villages in Sipispis district - Era Rahmadani Damanik; Atika Atika; Nurbaiti Nurbaiti (Indonesia Auditing Research Journal, 2026)
This study aims to analyze the effect of landscape authenticity, nature-based experience, and tourist participation on the preservation of tourist villages in Sipispis District. This research uses a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Square (SmartPLS). The sample was obtained through questionnaires distributed to tourists visiting tourist villages.The results show that landscape authenticity, nature-based experience, and tourist participation have a positive and significant effect on the preservation of tourist villages. Landscape authenticity is the most dominant variable. The R-Square value of 0.654 indicates that the model has moderate explanatory power.This study implies that tourist village management should maintain landscape authenticity, improve nature-based tourism experiences, and encourage active tourist participation to support sustainability.